Avulsion fracture of anterior talofibular ligament from talus: A case report. (March 2019) - Köse, Özkan; Turan, Adil; Acar, Baver; Unal, Melih; May, Hasan
Highlights: ATFL avulsion fracture from talus is a rare type of injury following common lateral ankle sprains. This pattern of injury is usually missed or mixed with fibular avulsion fractures due to the difficulty of detection on standard ankle radiographs. Oblique ankle radiographs and CT are useful imaging modalities that demonstrate the fracture, size of the fragment and its anatomic relationship. Screw fixation of this fracture may prevent residual ankle instability, if the size of the fragment is large enough. Abstract: Anterior talofibular ligament (ATFL) injuries can occur in three different distinct patterns; rupture of the ligament as a pure soft tissue injury, an avulsion fracture at the ATFL's attachment to either the fibula or the talus. Although fibular avulsion fractures are common, avulsion fracture of ATFL from talus is extremely rare with a single previously reported case in the current literature. A 34-year-old female with ATFL talar avulsion fracture associated with medial malleolar fracture was presented to the emergency department. Fixation of the fragment resulted with excellent functional outcome without a residual instability. Besides more common injury patterns such as mid-substance ATFL rupture and ATFL fibular avulsion fracture, talar avulsion fracture pattern should also be kept in mind in a patient presented with lateral ankle sprain. When a fragment is seen on the ankle radiographs at the tip of fibula, previously described special oblique views should be performed to reveal the correct origin of the fragment.